Idiopathic Hyperphosphatasia and TNFRSF11B Mutations: Relationships Between Phenotype and Genotype - Belinda Chong; Madhuri Hegde; Matthew Fawkner; Scott Simonet; Hamilton Cassinelli; Mahmut Çöker; John А. Kanis; J. Seidel; Cristina Tau; Beyhan Tüysüz; Bilgin Yüksel; Donald R. Love; et al. (2003)
Abstract Homozygous mutations in TNFRSF11B, the gene encoding osteoprotegerin, were found in affected members from six of nine families with idiopathic hyperphosphatasia. The severity of the phenotype was related to the predicted effects of the mutations on osteoprotegerin function. Introduction: Idiopathic hyperphosphatasia (IH) is a rare high bone turnover congenital bone disease in which affected children are normal at birth but develop progressive long bone deformities, fractures, vertebral collapse, skull enlargement, and deafness. There is, however, considerable phenotypic variation from presentation in infancy with severe progressive deformity through to presentation in late childhood with minimal deformity. Two recent reports have linked idiopathic hyperphosphatasia with deletion of, or mutation in, the TNFRSF11B gene that encodes osteoprotegerin (OPG), an important paracrine modulator of RANKL-mediated bone resorption. Materials and Methods: We studied subjects with a clinical diagnosis of IH and unaffected family members from nine unrelated families. Clinical, biochemical, and radiographic data were collected, and genomic DNA examined for mutations in TNFRSF11B. The relationship between the mutations, their predicted effects on OPG function, and the phenotype were then examined. Results: Of the nine families studied, affected subjects from six were homozygous for novel mutations in TNFRSF11B. Their parents were heterozygous, consistent with autosomal recessive inheritance. Four of the six mutations occurred in the cysteine-rich ligand-binding domain and are predicted to disrupt binding of OPG to RANKL. Missense mutations in the cysteine residues, predicted to cause major disruption to the ligand-binding region, were associated with a severe phenotype (deformity developing before 18 months age and severe disability), as was a large deletion mutation. Non-cysteine missense mutations in the ligand-binding domain were associated with an intermediate phenotype (deformity recognized around the age of 5 years and an increased rate of long bone fracture). An insertion/deletion mutation at the C-terminal end of the protein was associated with the mildest phenotype. Conclusion: Mutations in TNFRSF11B account for the majority of, but not all, cases of IH, and there are distinct genotype-phenotype relationships.